Bryozoa (Cheilostomata) from polymetallic nodules in the Russian exploration area, Clarion–Clipperton Fracture Zone, eastern Pacific Ocean—taxon novelty and characteristics as macro- and megafaunal elements - Grischenko, Andrei V.; Gordon, Dennis P.; Melnik, Viacheslav P. (Zootaxa, 2024)
This work describes Bryozoa of the order Cheilostomata associated with polymetallic nodules collected by box-coring in the eastern part of the Russian exploration area of the Clarion-Clipperton Fracture Zone (CCFZ or CCZ) under contract to Yuzhmorgeologiya. Study of 569 cheilostome specimens from 4510–5280 m depth yielded 32 species (22 new) in 20 genera (3 new) and 14 families (1 new). For six species, the nomenclature was left open (genus only) owing to the paucity of defining characters. One species with a costate frontal shield, possibly belonging to the otherwise monotypic Polliciporidae, clearly represents a new genus, but was not named, as it comprises only an ancestrula, one fully formed daughter zooid and a zooid bud. Four of the species we detected are known from the deep sea beyond the CCZ; Columnella magna and Acanthodesiomorpha problematica occur not only elsewhere in the Pacific Ocean but also the Atlantic Ocean, while Smithsonius quadratus was first described from the Kuril-Kamchatka Trench, and the authors have unpublished records of Smithsonius candelabrum n. sp. from the Magellan Seamounts and the Louisville Ridge. These records give hope that other CCZ bryozoan taxa may also occur elsewhere, offsetting local extirpation through nodule mining. Almost 63% (20 species) of CCZ Cheilostomata have a flexibly erect colony attached by one or several rhizoids (and/or the ancestrula has a proximal cuticular stalk-like portion). Ten other species have fixed-erect rigid colonies; only two species are encrusting. If a 50 mm height or spread is taken as the lower limit defining a megafaunal organism, then only C. magna qualifies as megafaunal. If 20 mm is taken as the lower size limit (definitions vary), then nine other species have the potential to be recognized in ROV-obtained images. The completion of this monograph allows a summary of all bryozoan data for the Russian sector of the CCZ. Altogether, 52 species are known from this area, totalling 1002 specimens from 437 stations. The most abundant and most ubiquitous species was the cyclostome Pandanipora helix, comprising 230 specimens from 137 stations and accounting for almost 23% of all specimens collected. The next most abundant and ubiquitous species were the cheilostomes Aulopocella polymorpha (124 specimens, 105 stations) and Fulgurella marina (104 specimens, 92 stations). These three species accounted for almost 46% of all specimens collected. All other species yielded fewer than 45 specimens each from 33 or fewer stations. Twelve species were represented by a single colony. Although some ROV images from eastern sectors of the CCZ have been recognized as bryozoans and published as such, few have been studied systematically. Bryozoans have also been reported from seamounts, level-bottom rock flats, ridges and troughs in the CCZ, but their identities remain unknown. It is imperative that institutions seek the collaboration of taxonomists rather than allow material to languish unidentified in collections.